Technological Pedagogical Content Knowledge (TPACK) Guru Pada Pembelajaran Tematik Kelas V Di Madrasah Ibtidaiyah Negeri 3 Jembrana - Irma Lutfiyatin Najwa; Nino Indrianto (Latifah Pres, 2022)
Teachers have to master two kinds of knowledge, namely pedagogic and content knowledge. However, with the development of technology, the teachers also have to master the use of technology. The teachers ability in integrating technology can be seen from the technological pedagogical content knowledge (TPACK). The TPACK model is used to describe teacher's knowledge in integrating technology in the learning process because the tpack include as part of the teacher's professional competence. The purpose of this research is how the teacher's Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK) on the thematic learning process for fifth grade students at Madrasah Ibtidaiyah Negeri 3 Jembrana. The research approach was qualitative with case study as the research design. The technique of data collection was through observation, interviews, and documentation. The data analysis wascarried out by data condensation, data presentation, and drawing conclusions. To test the validity of the data, the researcher used two kind of triangulation, namely source and technic triangulation. The results of this research indicate that the Technological Knowledge (TK) component in the thematic learning process, the fifth grade teacher uses hardware and software in the thematic learning process. While in the Pedagogical Knowledge (PK) component, the class V teacher manages the class by conditioning students to learn, designing lesson plans such as syllabus, Learning Implementation Plans, and power point media, carrying out learning consisting of introductions, core activities, and closing, and carry out evaluations on aspects of attitudes, knowledge, and skills. Furthermore, in the Content Knowledge (CK) component, the class V teacher has sufficient knowledge of the material, because previously the teacher had looked for reference sources and studied them, explained the material using the lecture method and used power point media, provided examples in the form of pictures and videos. Keywords: TPACK; Teacher competence; Thematic Learning